Ama dalam Drama Amachan Karya Kankuro Kudo - I Putu Alvan Adi, Andreas (Humanis, 2018)
The tittle of this thesis is “Ama in Drama of Amachan which is made by Kankuro Kudo”. This research is aimed to understand the social background of society in coastal area of Kitasanriku in the drama of Amachan which is made by Kankuro Kudo and the character of ama in coastal area of Kitasanriku in the drama of Amachan which is made by Kankuro Kudo. The method used in this research is descriptive-qualitative method. This research uses the sociological theory of Wellek and Warren literature (1990), semiotic theory of Ferdinand de Saussure (1913). Based on the result of the research, there is social background of the Kitasanriku society in the drama of Amachan. They are the habit of the society of coastal area of Kitasanriku, the traditions of of the society of coastal area of Kitasanriku, the attitude and believe of the Kitasanriku society, dialect of Sodegahama as the identity of Kitasanriku society, and social stratification of the Kitasanriku society. The profession of Ama has a big contribution for the society of Kitasanriku in Drama of Amachan which is made by Kankuro Kudo, they are roles in tourism sector and economical sector.